2017
DOI: 10.1093/annonc/mdx155
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor gene status in plasma DNA associates with worse outcome on enzalutamide or abiraterone for castration-resistant prostate cancer: a multi-institution correlative biomarker study

Abstract: BackgroundThere is an urgent need to identify biomarkers to guide personalized therapy in castration-resistant prostate cancer (CRPC). We aimed to clinically qualify androgen receptor (AR) gene status measurement in plasma DNA using multiplex droplet digital PCR (ddPCR) in pre- and post-chemotherapy CRPC.MethodsWe optimized ddPCR assays for AR copy number and mutations and retrospectively analyzed plasma DNA from patients recruited to one of the three biomarker protocols with prospectively collected clinical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
211
3
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(244 citation statements)
references
References 28 publications
12
211
3
7
Order By: Relevance
“…Our data analysis confirmed the negative prognostic and predictive impact of copy number alterations of the AR gene for both abiraterone and enzalutamide groups of patients, as already described in literature …”
Section: Discussionsupporting
confidence: 90%
“…Our data analysis confirmed the negative prognostic and predictive impact of copy number alterations of the AR gene for both abiraterone and enzalutamide groups of patients, as already described in literature …”
Section: Discussionsupporting
confidence: 90%
“…Among the patients in the study discovery cohort who had received docetaxel ( n = 98), AR amplification was associated with a worse rate of PSA decline of ≥50%, shorter PFS (HR = 1.95; 95% CI, 1.23–3.11; p < 0.01), and shorter OS (HR = 3.81; 95% CI, 2.28–6.37; p < 0.001). These results were confirmed in their replication cohort of enzalutamide-treated patients from the PREMIERE trial ( n = 100), where patients with AR amplification experienced shorter PSA PFS (HR = 4.33; 95% CI, 1.94–9.68; p < 0.001), and OS (HR = 11.08; 95% CI, 2.16–56.95; p < 0.004) [54]. Additional studies of liquid biopsies have also demonstrated that AR amplification in ctDNA is associated with resistance to abiraterone and enzalutamide [55,56].…”
Section: Ar-dependent Resistance Mechanismsmentioning
confidence: 79%
“…Using so-called 'liquid biopsies', primary and acquired resistance to AR-targeted therapy has been linked to amplification or mutation of the AR gene (3)(4)(5)(6)(7), and also to the expression (in circulating tumor cells) of truncated AR splice variants that display ligand-independent activity (8,9). The impact of these biomarkers in first-line mCRPC patients has not been adequately studied and it is unclear whether the detection of AR alterations in patient ctDNA can outperform standard clinical prognostic factors.…”
Section: Introductionmentioning
confidence: 99%